NGC 300 ULX1: spin evolution, super-Eddington accretion, and outflows - Vasilopoulos, G.; Petropoulou, M.; Koliopanos, F.; Ray, P. S.; Bailyn, C. B.; Haberl, F.; Gendreau, K. (Monthly Notices of the Royal Astronomical Society, 2019)
NGC 300 ULX1 is an ultraluminous X-ray pulsar, showing an unprecedented spin evolution, from about 126 s to less than 20 s in only 4 yr, consistent with steady mass accretion rate. Following its discovery we have been monitoring the system with Swift and NICER to further study its properties. We found that even though the observed flux of the system dropped by a factor of ≳20, the spin-up rate remained almost constant. A possible explanation is that the decrease in the observed flux is a result of increased absorption of obscuring material due to outflows or a precessing accretion disc.
Keywords: Astrophysics - High Energy Astrophysical Phenomena; galaxies: individual: NGC 300; pulsars: individual: NGC 300 ULX1; stars: neutron; X-rays: binaries